The evolution of minimally invasive tissue sampling in postmortem examination: a narrative review - Christina R. Paganelli; Norman J. Goco; Elizabeth M. McClure; Kathryn K. Banke; Dianna M. Blau; Robert F. Breiman; Clara Menéndez; Natalia Rakislova; Quique Bassat (Global Health Action, 2020)
Background Because of low acceptance rates and limited capacity, complete diagnostic autopsies (CDAs) are seldom conducted in low- and middle-income countries (LMICs). There have been growing investments in less-invasive postmortem examination methodologies, including needle-based autopsy, known as minimally invasive autopsy or minimally invasive tissue sampling (MITS). MITS has been shown to be a feasible and informative alternative to CDA for cause of death investigation and mortality surveillance purposes. Objective The aim of this narrative review is to describe historical use and evolution of needle-based postmortem procedures as a tool to ascertain the cause of death, especially in LMICs. Methods Key word searches were conducted in PubMed and EBSCO in 2018 and 2019. Abstracts were reviewed against inclusion and exclusion criteria. Full publications were reviewed for those abstracts meeting inclusion criteria and a start set was established. A snowball search methodology was used and references for all publications meeting inclusion criteria were manually reviewed until saturation was reached. Results A total of 1,177 publications were initially screened. Following an iterative review of references, 79 publications were included in this review. Twenty-nine studies, published between 1955 and 2019, included MITS as part of postmortem examination. Of the publications included, 76% (60/79) have publication dates after 2010. More than 60% of all publications included addressed MITS in LMICs, and a total of nine publications compared MITS with CDA. Conclusions Although there is evidence of less-invasive postmortem sampling starting in the 1800s, more structured needle-based postmortem examination publications started to appear in the mid-twentieth century. Early studies were mostly conducted in high-income countries but starting in 2010 the number of publications began to increase, and a growing number of studies were conducted in LMICs. Initial studies in LMICs were disease-specific but since 2015 have evolved to include more expansive postmortem examination.